Toward a realistic theory of social entrepreneurship (NGOs) grounded on microfinance research: Selling dreams to society1. (2nd July 2019) - Ashta, Arvind
Abstract: Social entrepreneurs sell dreams of solving a social problem of a segment of society to entice a broader segment of society to subsidize their ventures. They are motivated by a combination of passion and compassion, need for creativity, problem solving, and esteem. They sell their dreams by storytelling and narratives in order to obtain subsidized resources. In order to achieve their goals, they need to demonstrate the impact for the continuance of subsidies. Too much financial profit leads to withdrawal of subsidies.